2012
DOI: 10.2108/zsj.29.702
|View full text |Cite
|
Sign up to set email alerts
|

High Degree of Mitochondrial Haplotype Diversity in the Japanease Common Toad Bufo japonicus in Urban Tokyo

Abstract: The Japanese common toad Bufo japonicus is widely distributed across mainland Japan and is classified into two subspecies, B. japonicus japonicus and B. japonicus formosus, in the western and eastern regions, respectively. To investigate the genetic diversity of B. japonicus at the breeding pond (local population) level, we sequenced 831 base pairs of mitochondrial DNA (mtDNA) cytochrome b (Cyt b) from 75 individuals collected from nine ponds in urban Tokyo and the surrounding area. Phylogenetic and population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Our previous phylogenetic analysis revealed that Japanese common toads in the Tokyo area have two major mitochondrial lineage types: Western and Eastern, which correspond to B. japonicus japonicus (hereafter, japonicus ) and B. japonicus formosus (ditto, formosus ), respectively (Hase et al 2012). These findings are consistent with the two lineage patterns identified by RFLP genotyping.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous phylogenetic analysis revealed that Japanese common toads in the Tokyo area have two major mitochondrial lineage types: Western and Eastern, which correspond to B. japonicus japonicus (hereafter, japonicus ) and B. japonicus formosus (ditto, formosus ), respectively (Hase et al 2012). These findings are consistent with the two lineage patterns identified by RFLP genotyping.…”
Section: Resultsmentioning
confidence: 99%
“…11. Molecular phylogenetic analysis of Cyt b sequences was performed together with previously reported analyses (Igawa et al 2006; Hase et al 2012). The phylogenetic analysis strongly supported the above-mentioned results and the findings are detailed in Figure A1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations